(untitled) (Journal of Asian Development Studies, 2025)
Indian religions, such as Buddhism and Hinduism, are rich in their long-standing traditional development of deities and scriptures, drawing inspiration from earlier Vedism and Brahmanism. There are several levels of divinity, including divine and semi-divine beings. The semi-divine beings include tree spirits (Yakshas), pond spirits (Nagas), and celestial musicians (Gandharvas), among others. These are not only mentioned in different texts but also depicted in different types of Art. Yakshas are the oldest anthropomorphic figures, which were depicted in the oldest schools of Indian Art, such as Bharhut and Sanchi, where other prominent divine figures, including that of the Buddha, were prohibited. In these schools of Art, Yakshas were depicted as guardian deities in specific scenes. Later on, other divine images, including that of Buddha, were introduced in the later schools of Art, which also included Yakshas in subservient roles. Mathura and Gandhara are the later schools, which have essential examples of Yakshas depicted in various important scenes of Buddhist Art. The focus of this paper is on the Yakshas and Yākshinīs, or, in other words, the tree spirits. The paper discusses their nature, status, and development throughout the ages, as reflected in Hindu and Buddhist texts such as the Vedas, Brahmanas, Upanishads, and Buddhist sutras. It also includes the depiction of Yakshas and Yākshinīs in the various artistic traditions of pre-Buddhist and Buddhist Art schools of the Indo-Pak subcontinent, such as those of Bharhut, Sanchi, Mathura, and Gandhara. It will also include a possible iconographic symbolism and Socio-Religious Background, focusing on semi-divine beings in the executed Art.